Adjectives in Shakespeare's Sonnets: A Discourse Analysis - Hassan, Nagham Ali (Al-Adab Journal, 2022)
The present paper studies the use of adjectives in Shakespeare's Sonnets (4, 5, 6, & 9), which are chosen randomly, on the three levels: grammar, lexis and conversation. It tackles adjectives as a literary term with presenting their forms and functions. The presentation is done according to the themes, their forms and functions in conversation, the adjectives are shown in this paper as for their forms, frequency and meanings in the sonnets and their effects on studying. The analysis is done according to Quirk et al. (1985) and Quirk and Greenbaum (1973). Then, all adjectives have been calculated in the sonnets. The results of the analysis have shown that compound adjectives which occurred (31) are used more than the Suffixation and Prefixation as (13) and (8) respectively. The paper shows that there is a clear relation between adjectives and the thematic structure of the sonnets. The presentation of adjectives proves Shakespeare's witty ways to use them in a method that equals various themes. Moreover, they are used precisely and accurately to transmit themes and have pedagogical effects in conversation.